Examining Complaint Handling Processes among Ghanaian Rural Banks and its Influence on Customer Satisfaction - Edmund, Nkrumah, Nana Kwame; Ernest, Obeng; Serwah, Akoto Linda; Anaba, Oswin Aganda (International Journal of Economics, Business and Management Studies, 2019)
The purpose of the study is to understand how effective customer complaint handling procedure among Ghanaian rural banks enhances customer satisfaction. A cross-sectional research on 72 rural banks and 3,622 rural banking customers through questionnaire is conducted. The sample framework included customers of the rural banks who frequently visit the bank premises for transactions and have accounts with the bank for at least 5 years. Responses are analyzed using Chi-square goodness of fit test, ANOVA, multiple regression and Pearson moment correlation. The regression results predicted that effective complaint handling procedures among rural banks will significantly influence the level of satisfaction among customers. The Pearson-moment correlation as well confirms that there exist a significant and stronger relationship between complaint handling procedures and customer satisfaction among rural banking. This study focuses on rural banking customer service management and satisfaction in Ghana. The area of complaint handling processes among rural banks remains a gap in previous literature which needed to be filled.